GENDER EMPOWERMENT THROUGH LIVESTOCK CARE AND MANAGEMENT: A CASE STUDY OF DISTRICT JHANG - Menhas, Rashid (Innovare Journal of Social Sciences, 2014)
Livestock is an important component of Pakistan population since 30-35 million rural population is involved in livestock rising. It provides a higher share of household income to poor and landless families. Livestock is widely distributed in the country. Almost all farmers inPakistanhave cattle or but few have sheep's and goats. Dairy is also a major enterprise. This provides cash profit to the farmers who keep one-third of the total animals. Only buffaloes provide three-fourth of the milk production in the country. Livestock are used for ploughing, land leveling, threshing, fodder chopping, cane crushing transportations and water lifting. The objective of present study was to investigate the participation of respondents in livestock management. Multistage sampling technique was used for this study. At the first stage, out of four Tehsils, two Tehsils were selected randomly. Then from two selected Tehsils, four villages were selected. Finally at the third stage, 150 respondents (rural women) were selected by using convenient sampling. The data thus collected were analyzed and interpreted by using appropriate statistical package to draw the conclusions. The results revealed that majority of the respondents were participated in fodder cutting activities and were keeping animals in their courtyard. Through livestock care and management females uplifting living standard of their families.